Multicolor Carbon Dots Prepared by Single‐Factor Control of Graphitization and Surface Oxidation for High‐Quality White Light‐Emitting Diodes. Issue 19 (25th June 2021) - Zheng, Yuxin; Arkin, Kamile; Hao, Jiawei; Zhang, Siyi; Guan, Wei; Wang, Lingling; Guo, Yingna; Shang, Qingkun
Abstract: In a reaction system of asparagine and p‐phenylenediamine, blue, green, orange, and red carbon dots (CDs) are successfully prepared by adjusting the ratio of the two reactants. The obtained multicolor CDs have excellent stable properties and high fluorescence quantum yields (up to 74%). Clarifying the luminescence mechanism of multicolor CDs is based on the investigation of the composition, structure, and fluorescence properties of the CDs combined with quantum chemistry calculations. A high‐quality white light‐emitting diode (LED) with CIE color coordinates (0.33, 0.33) is successfully fabricated using a multicolor CD‐epoxy resin composite, and its color temperature and color rendering index are 5612 K and 94, respectively. It is of great significance to prepare multicolor CDs with high fluorescence quantum yields by single‐factor control. Using multicolor CDs to fabricate standard white LEDs close to sunlight will significantly increase the practical application value of CDs. Abstract : Four color carbon dots (CDs) are synthesized only by controlling the ratio of asparagine and p‐phenylenediamine. The obtained multicolor CDs have good fluorescence properties. Combining multicolor CDs with resin can obtain CDs‐resin composites with different fluorescent colors. Based on this, a standard white light‐emitting diode is fabricated, with a color temperature of 5612 K and a color rendering index of 94.